Editorial preface: A special issue on themes (i) Nano-energy / Environmental for a better Society and (iii) Nano-catalysis for Green technology. (2017) - Sen, Tapas; Polshettiwar, Vivek; Mahmoudi, Morteza
Abstract: The contributors to this special issue are from early carrier researchers to experts in their relative areas from across the world and represent a current and up to date research overview on functional nanomaterials in energy / environmental for a better society and nano-catalysis for green technology. The topics were the two important themes in our 1 st International symposium entitled Functional Nanomaterials in Industrial Applications: Academic – Industry Meet (29-31 March 2016), University of Central Lancashire, Preston, United Kingdom. A special focus issue on theme 2 (Nanomedicine for Health and Diagnostics) will be published in the journal "Nanomedicine" by Future Medicine in November 2016.